The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1990
DOI: 10.1055/s-2007-1013982
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Effect of Supraaortic Ridge Enhancement on the Closure Mechanism of the Aortic Valve and its Implications in Aortic Valve Repair

Abstract: The presence of the sinus of valsalva plays an essential part in the closing mechanism of the aortic valve. High-energy vortices are initiated at the upper limit of each sinus or supraaortic crest, and last during the whole valve closing time. An attempt was made to prove this hypothesis in vivo by intermittent augmentation of each supraaortic ridge. In a series of five dogs without cardiopulmonary bypass, pledgeted sutures were placed at the level of each crest and passed through tourniquets. In a series of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Previoius authors have suggested that the presence of the sinuses of Valsalva are to assist in cushioning early diastolic transvalvular pressures (Beck et al, 2001; Duran et al, 1990; Sacks et al, 2009). Simulations have shown that the absence of the sinuses results in additional stresses on the leaflets , as does a reduction in the sinus wall compliance (Beck et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Previoius authors have suggested that the presence of the sinuses of Valsalva are to assist in cushioning early diastolic transvalvular pressures (Beck et al, 2001; Duran et al, 1990; Sacks et al, 2009). Simulations have shown that the absence of the sinuses results in additional stresses on the leaflets , as does a reduction in the sinus wall compliance (Beck et al, 2001).…”
Section: Discussionmentioning
confidence: 99%